Effect of the sequence of aerobic and resistance exercise on physical fitness in women over the age of 50 - Anderson Leandro Peres Campos; Airton José Rombaldi; Marcelo Cozzensa Silva (Universidade Federal de Santa Catarina, 2010)
Concurrent training has been frequently used, although little is known about the effects of the exercise sequence on physical fitness in elderly women. The objective of this study was to determine the effect of the sequence of aerobic and resistance exercise on physical fitness in women over 50 years old. The sample consisted of 26 women randomly divided into two groups: A1 (aerobic and resistance training) and M1 (resistance and aerobic training). Body weight, height, body mass index (BMI), sum of skinfolds, flexibility, and leg, back and hand grip strength were measured. Descriptive statistics and one-way ANOVA were used for data analysis, adopting a level of significance of 5%. The results showed significant changes in back strength (p=0.01) and leg strength (p=0.0002) after 12 weeks in group A1, and in leg strength (p=0.02) in group M1. Except for BMI (p=0.05), no differences in anthropometric measures, strength or flexibility were observed between groups after testing. In conclusion, improvement of strength and the lack of change in the other indices were observed in the women studied, irrespective of the sequence of concurrent training. This finding is important for older adults since it directly affects improvement in the quality of life and health of this population.